Variational order for forced Lagrangian systems - Martín de Diego, David; Sato Martín de Almagro, Rodrigo Takuro (Nonlinearity, 2018)
We are able to derive the equations of motion for forced mechanical systems in a purely variational setting, both in the context of Lagrangian or Hamiltonian mechanics, by duplicating the variables of the system as introduced by C. Galley. We show that this construction is useful to design high-order integrators for forced Lagrangian systems and, more importantly, we give a characterization of the order of a method applied to a forced system using the corresponding variational order of the duplicated one.<br